Inhibition of cyclic 3',5'-nucleotide phosphodiesterase by glypentide and other oral antidiabetic agentS (Revista Española de Fisiología, 1974)
Inhibition of Cyclic 3',5'-Nucleot¡de Phosphodiesterase by Glypentide and Other Oral Antidiabetic Agents. Rev. esp. Fisiol., 30, 277-282. 1974.The effect of nine sulfonylureas and a biguanide on the ox hearl and rat brain phosphodiesterase activity has been studied. Enzymatic activity was determined spectro- photometrically at 265 nm, combining alkaline phosphatase and adenosine desaminase, both in higher concentrations than that of phosphodiesterase.The sulfonylureas studied and the biguadine, show a competitive inhibition on heart and brain PDE. There is a clear relationship between the Chemical structure of this compounds ant its inhibitory potency, beeing this inhibition more pronounced for the group of substituted arylamidoethyl sulfonylureas. In this group both the substi- tution of cyclopentane by cyclohexane on the ureic end of the molecule and/or the m-chloro substitution on the terminal benzene ring increase the inhibitory potency.No specific inhibitory activity of the studied compounds, on both PDEs has becn observed. The greater inhibitory potency always corresponds to glibenclamide; fen- formine and tolbutamide are the less active, whereas glypentide, a new oral hypo- glycaemic agent, has an intermedíate inhibitory effect.